Study of Custody of Children: Legislative Developments in India and England - Kumar, Dr. Subhash; Mittal, Nidhi (Innovative Research Thoughts, 2017)
A parent's legal and practical connection with his or her kid is sometimes referred to as "child custody," "guardianship," or "custody," and these phrases are often used to characterise this relationship. Children's welfare wasn't seen as a government role in any ancient civilisation. Fathers in ancient Rome, for example, had an almost unrestricted inherent right to make decisions about their children's well-being. The well-being of children was primarily a concern of their families, not one that fell within the purview of the state. In the ancient world, fathers were free to punish their children in any way they saw fit, even killing their infants.